Green ZnSeTe quantum dot, preparation method thereof and display device
By using a highly reactive first zinc precursor and a method of strictly controlling the molar ratio, green-light ZnSeTe quantum dots are generated, and through multi-layer structure design, the problems of large half-maximum width and poor luminescence performance of green-light ZnSeTe quantum dots in the prior art are solved, and the performance is significantly improved.
Patent Information
- Application Number
- CN202410160176.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-04
- Publication Date
- 2025-03-25
AI Technical Summary
In the prior art, the green light ZnSeTe quantum dot has a large half-maximum width and poor luminous performance, making it difficult to meet the needs of ultra-high-definition displays and other fields.
By using the first zinc precursor with a reactive activity higher than that of the selenium precursor and the tellurium precursor, the molar ratio of the selenium precursor, the tellurium precursor and the first zinc precursor are strictly controlled to generate a green-light ZnSeTe nucleus, and the formation and photoluminescence performance of quantum dots are improved through the transition of the gradient alloy layer and the design of the multi-layer structure.
The half-maximum width reduction of green light ZnSeTe quantum dots has been achieved, and the electroluminescent performance and electroluminescent performance has been improved by more than 30%.
Smart Images

Figure BDA0004698379950000121 
Figure BDA0004698379950000131
Abstract
Description
Technical Field
[0001] The present application belongs to the field of quantum dot technology, and specifically relates to a green light ZnSeTe quantum dot and a preparation method and a display device thereof. Background Art
[0002] Quantum dots, also known as semiconductor nanocrystals, are a new type of semiconductor nanomaterial with a size of 1-10nm. Due to the quantum size effect and dielectric confinement effect, they have unique photoluminescence (PL) and electroluminescence (EL) properties. Compared with traditional organic fluorescent dyes, quantum dots have high quantum yield, high photochemical stability, not easy to photolyze, as well as wide excitation, narrow emission, high color purity, and the luminescent color can be adjusted by controlling the size of quantum dots. Excellent optical properties have broad application prospects in the field of display technology.
[0003] At present, cadmium-based quantum dots have gradually begun to be commercialized due to their advantages of high quantum efficiency, small half-peak width, strong blue light absorption and good stability. However, due to the presence of heavy metal element cadmium, such quantum dots no longer meet the increasingly important environmental protection requirements, so the development of new cadmium-free quantum dots is extremely urgent. Environmentally friendly quantum dots include: InP, carbon dots, perovskite, AgS, PbS, ZnSe, ZnSeTe, etc. However, compared with traditional cadmium-based quantum dots, environmentally friendly quantum dots in the prior art have many shortcomings such as large half-peak width, poor performance, and poor stability, which limit their application.
[0004] Among them, ZnSeTe quantum dots have great potential applications in ultra-high-definition display fields such as light-emitting diodes. Compared with green ZnSeTe quantum dots, green ZnSeTe quantum dots are more difficult to synthesize and have worse optical properties. The existing green ZnSeTe quantum dots have a large half-peak width and their luminescence performance needs to be improved.
[0005] In view of this, the present application provides a green light ZnSeTe quantum dot and a preparation method and a display device thereof. The green light ZnSeTe quantum dot has a small half-peak width, good quantum dot formation, few defects, and significantly improved photoluminescence performance and electroluminescent device performance. Summary of the invention
[0006] The purpose of the present application is to provide a green light ZnSeTe quantum dot and a preparation method and a display device thereof. The green light ZnSeTe quantum dot has a small half-peak width, good quantum dot formation, few defects, and significantly improved photoluminescence performance and electroluminescent device performance.
[0007] In a first aspect of the present application, a method for preparing green light ZnSeTe quantum dots is provided, the preparation method comprising the steps of:
[0008] S1, obtaining a selenium precursor, a tellurium precursor and a first zinc precursor, wherein the reaction activity of the first zinc precursor is higher than that of the selenium precursor and the tellurium precursor;
[0009] S2, at a first temperature, mixing a selenium precursor, a tellurium precursor and a first zinc precursor to form a first mixed system, wherein the molar ratio of the selenium precursor, the tellurium precursor and the first zinc precursor is (1-4):1:(7-10), and reacting to generate a green light ZnSeTe nucleus.
[0010] In some embodiments, the selenium precursor includes at least one of selenium-trioctylphosphine (Se-TOP), selenium-tributylphosphine (Se-TBP), selenium-triphenylphosphine (Se-TPP), and selenium-diphenylphosphine (Se-DPP).
[0011] In some embodiments, the tellurium precursor includes at least one of tellurium-trioctylphosphine (Te-TOP), tellurium-tributylphosphine (Te-TBP), and tellurium-triphenylphosphine (Te-TPP).
[0012] In some embodiments, the first zinc precursor includes at least one of dimethyl zinc, diethyl zinc, zinc acetate, zinc acetylacetonate, and zinc fluoride.
[0013] In some embodiments, in step S2, the molar ratio of the selenium precursor, the tellurium precursor and the first zinc precursor is (2.5-3.5):1:(8-9).
[0014] In some embodiments, in step S2, the selenium precursor is added prior to the tellurium precursor, and the first zinc precursor can be added in any order.
[0015] In some embodiments, the first temperature is 220-260° C., and the reaction time of the first mixed system is 15-40 min.
[0016] In some embodiments, the first mixed system further includes an activator, and the activator is used to improve the reactivity of the selenium precursor and the tellurium precursor.
[0017] Further, in step S2, the activator is added first, and then the selenium precursor, the tellurium precursor and the first zinc precursor are added.
[0018] The active agent includes at least one of diphenylphosphine, triphenylphosphine, tributylphosphine and tripentylphosphine.
[0019] Furthermore, the molar ratio of the active agent added to the tellurium precursor is (2-4): 1. Preferably, the molar ratio of the active agent added to the tellurium precursor is (2.5-3.5):1.
[0020] In some embodiments, at the first temperature, an etchant is added to the reaction system, and the etchant is used to etch the green light ZnSeTe core.
[0021] In some embodiments, the method for preparing green light ZnSeTe quantum dots further comprises the steps of:
[0022] S3, preparing a transition layer: at a second temperature, adding a second zinc precursor and a selenium precursor to S2, wherein the selenium precursor is added dropwise at a rate of 4-6 mL / h to form a ZnSe transition layer covering the green light ZnSeTe core body;
[0023] S4, preparing an outer shell layer: at a third temperature, adding a third zinc precursor and a sulfur precursor to S3, wherein the third zinc precursor is an amine-containing zinc precursor, to form a ZnS outer shell layer covering the transition layer.
[0024] In some embodiments, the second zinc precursor includes at least one of zinc oleate, zinc carbonate, zinc oxide, zinc palmitate, zinc laurate, and zinc n-hexanoate.
[0025] In some embodiments, in step S3, the second temperature is 300-330°C, and the molar ratio of the added selenium precursor to the second zinc precursor is 1:(1.2-4). Preferably, the molar ratio of the added selenium precursor to the second zinc precursor is 1:(1.5-2.5).
[0026] Further, at the second temperature, 2 / 5-4 / 5 of the second zinc precursor is added, and then the selenium precursor is added dropwise at a rate of 4-6 mL / h. When the selenium precursor is added to half, the remaining second zinc precursor is added.
[0027] In some embodiments, in step S3, after forming the ZnSe transition layer, the temperature is raised to 320-340°C, and a second zinc precursor and a sulfur precursor are added to form a ZnSe transition layer-coated ZnSe 1-x S x Transition layer, 0<X<1; wherein the molar ratio of the added sulfur precursor to the second zinc precursor is 1:(1.5-4), and the sulfur precursor is added dropwise at a rate of 5-7 mL / h. Preferably, the molar ratio of the added sulfur precursor to the zinc precursor is 1:(1.5-2.5).
[0028] Further, when the temperature reaches 320-340° C., 2 / 5-4 / 5 of the second zinc precursor is added, and then the sulfur precursor is added dropwise at a rate of 5-7 mL / h. When the sulfur precursor is added halfway, the remaining second zinc precursor is added.
[0029] The sulfur precursor includes at least one of dodecanethiol, hexadecanethiol, sulfur-trioctylphosphine (S-TOP), sulfur-tributylphosphine (S-TBP), sulfur-triphenylphosphine (S-TPP), and sulfur-trioctylamine (S-TOA).
[0030] In some embodiments, in step S4, the third temperature is 240-290°C, the amine-containing zinc precursor is added dropwise at a rate of 28-32 mL / h, and the sulfur precursor is added dropwise at a rate of 6-10 mL / h to form a ZnS outer shell layer.
[0031] Further, the molar ratio of the sulfur precursor to the amine-containing zinc precursor is 1:(0.5-1.5). Preferably, the molar ratio of the sulfur precursor to the amine-containing zinc precursor is 1:(0.6-0.8).
[0032] Furthermore, the amine-containing zinc precursor includes at least one of zinc oleylamine (Zn / OlAm), zinc n-octylamine, zinc tetradecylamine, and zinc hexadecylamine.
[0033] In some embodiments, the method for preparing green light ZnSeTe quantum dots further comprises the steps of:
[0034] S5, adding the amine-containing zinc precursor and the thiol ligand to step S4 to increase the thickness of the ZnS outer shell layer.
[0035] Furthermore, in step S5, the amine-containing zinc precursor is added dropwise at a rate of 22-26 mL / h, and the thiol ligand is added dropwise at a rate of 2-5 mL / h.
[0036] Further, the molar ratio of the thiol ligand added to the amine-containing zinc precursor is 1:(0.8-3). Preferably, the molar ratio of the thiol ligand added to the amine-containing zinc precursor is 1:(0.8-1.5).
[0037] The thiol ligand comprises at least one of methyl mercaptan, ethyl mercaptan, propyl mercaptan, butyl mercaptan, pentyl mercaptan, hexyl mercaptan, octyl mercaptan, dodecanethiol, hexadecanethiol, octadecanethiol and benzyl mercaptan.
[0038] In some embodiments, the maximum emission peak wavelength of the green light ZnSeTe quantum dots is 500-540 nm. Preferably, the maximum emission peak wavelength of the green light ZnSeTe quantum dots is 515-535 nm. More preferably, the maximum emission peak wavelength of the green light ZnSeTe quantum dots is 520-530 nm.
[0039] In a second aspect of the present application, a green light ZnSeTe quantum dot is provided, wherein the green light ZnSeTe quantum dot is prepared by the above method.
[0040] In some embodiments, the maximum emission peak wavelength of the green light ZnSeTe quantum dots is 500-540 nm. Preferably, the maximum emission peak wavelength of the green light ZnSeTe quantum dots is 515-535 nm. More preferably, the maximum emission peak wavelength of the green light ZnSeTe quantum dots is 520-530 nm.
[0041] According to a third aspect of the present application, a display device is provided, comprising the above-mentioned green light ZnSeTe quantum dots.
[0042] Compared with the prior art, the green light ZnSeTe quantum dots and the preparation method thereof of the present application have at least the following advantages:
[0043] (1) In the synthesis of the green light ZnSeTe core body, the present application uses a first zinc precursor, the reaction activity of the first zinc precursor is higher than that of the selenium precursor and the tellurium precursor, so the first zinc precursor can react with the selenium precursor and the tellurium precursor respectively in a balanced manner, and at the same time strictly control the molar ratio of the selenium precursor, the tellurium precursor and the first zinc precursor, so that Te and Se are evenly distributed in the core body, thereby reducing the half-peak width of the green light ZnSeTe quantum dot and improving the photoinduced performance and electroinduced performance. Among them, the electroinduced performance is particularly improved, which is improved by more than 30%.
[0044] (2) The present application uses a first zinc precursor having a higher activity than the selenium precursor and the tellurium precursor, and strictly controls the molar ratio of the selenium precursor, the tellurium precursor and the first zinc precursor. While making the ZnSeTe core emit green light, the selenium precursor, the tellurium precursor and the first zinc precursor react almost completely, and no purification and extraction steps are required, thereby greatly simplifying the synthesis steps.
[0045] (3) When synthesizing the ZnSe transition layer in the present application, the selenium precursor is added at a certain speed, the transition of the gradient alloy layer is very slow, the lattice adaptability is better and more stable, and at the same time, the stress is smaller and the transition layer defects are fewer, so that the reaction is more complete and the thickness of the transition layer is increased.
[0046] (4) The present application also provides a ZnSe transition layer. 1-x S x The transition layer makes the band gap energy increase more smoothly, that is, the lattice adaptability is better and more stable, the lattice defects are fewer, and the optical properties are better. At the same time, the sulfur precursor is added at a certain speed, and ZnSe 1-x S x The bandgap energy of the transition layer slowly increases, further improving the optical performance.
[0047] (5) In the present application, when preparing the ZnS outer shell layer, the zinc precursor is an amine-containing zinc precursor, which improves the reaction activity and facilitates the growth of the outer shell layer. In addition, after the synthesis is completed and the temperature is lowered to room temperature, the oleic acid ligand will replace the amine substance of the amine-containing zinc precursor, and the oleic acid ligand will bind more strongly to the quantum dots at room temperature.
[0048] (6) After preparing the ZnS outer shell layer, the present application further adds step S5 to increase the thickness of the ZnS outer shell layer; at the same time, the binding force between the thiol ligand and the quantum dots is stronger, thereby increasing the coverage and binding firmness of the ligand. DETAILED DESCRIPTION
[0049] The following examples are described to assist the understanding of the present application, and the examples are not and should not be interpreted in any way as limiting the scope of protection of the present application.
[0050] As stated herein, for example, "at least one (individual)" modifies the entire list of elements when preceding or following a list of elements without modifying the individual elements of the list. If not otherwise defined, all terms (including technical and scientific terms) in the specification may be defined as those skilled in the art generally understand. The terms defined in the commonly used dictionaries should be interpreted as being consistent with their meanings in the context of the relevant art and the present disclosure, and may not be interpreted in an ideal manner or too broadly unless clearly defined. In addition, unless explicitly described to the contrary, the wording "including" and the wording "comprising" when used in this specification indicate the presence of the stated features, regions, wholes, steps, operations, elements, and / or components, but do not exclude the presence or addition of one or more other features, regions, wholes, steps, operations, elements, components, and / or their collections. Therefore, the above wording will be understood to mean including the stated elements, but not excluding any other elements.
[0051] In a first aspect of the present application, a method for preparing green light ZnSeTe quantum dots is provided, the preparation method comprising the steps of:
[0052] S1, obtaining a selenium precursor, a tellurium precursor and a first zinc precursor, wherein the reaction activity of the first zinc precursor is higher than that of the selenium precursor and the tellurium precursor;
[0053] S2, at a first temperature, mixing a selenium precursor, a tellurium precursor and a first zinc precursor to form a first mixed system, wherein the molar ratio of the selenium precursor, the tellurium precursor and the first zinc precursor is (1-4):1:(7-10), and reacting to generate a green light ZnSeTe nucleus.
[0054] In some embodiments, the selenium precursor includes at least one of selenium-trioctylphosphine (Se-TOP), selenium-tributylphosphine (Se-TBP), selenium-triphenylphosphine (Se-TPP), and selenium-diphenylphosphine (Se-DPP).
[0055] In some embodiments, the tellurium precursor includes at least one of tellurium-trioctylphosphine (Te-TOP), tellurium-tributylphosphine (Te-TBP), and tellurium-triphenylphosphine (Te-TPP).
[0056] In some embodiments, the first zinc precursor includes at least one of dimethyl zinc, diethyl zinc, zinc acetate, zinc acetylacetonate, and zinc fluoride.
[0057] When synthesizing a green light ZnSeTe core, the emission wavelength needs to be increased to about 525nm compared to the synthesis of a green light ZnSeTe core, so the amount of tellurium precursor needs to be increased a lot, but the reactivity of the tellurium precursor is lower than that of the selenium precursor, and the selenium precursor is more easily combined with the zinc precursor, resulting in uneven distribution of Te and Se in the green light ZnSeTe core, making the green light ZnSeTe quantum dot half-peak width large, and low photo-induced and electro-induced performance. When synthesizing a green light ZnSeTe core, the present application uses a first zinc precursor, and the reactivity of the first zinc precursor is higher than that of the selenium precursor and the tellurium precursor, so the first zinc precursor can react with the selenium precursor and the tellurium precursor respectively in a balanced manner, and at the same time strictly controls the molar ratio of the selenium precursor, the tellurium precursor and the first zinc precursor, so that Te and Se are evenly distributed in the core, thereby reducing the half-peak width of the green light ZnSeTe quantum dot and improving the photo-induced and electro-induced performance. Among them, the improvement of electro-induced performance is particularly prominent, with an increase of more than 30%; due to the better matching of the activity of the nucleation precursors, the nucleation quality of the alloy ZnSeTe is better, a gradient alloy core is formed, and the distribution of each element will be more uniform, which can reduce the electron-hole injection barrier, make the electron-hole transport recombination more efficient, and achieve efficient device emission.
[0058] In some embodiments, in step S2, the molar ratio of the selenium precursor, the tellurium precursor and the first zinc precursor is (2.5-3.5):1:(8-9).
[0059] The present application uses a first zinc precursor having a higher activity than a selenium precursor and a tellurium precursor, and strictly controls the molar ratio of the added selenium precursor, the tellurium precursor and the first zinc precursor. While making the ZnSeTe core emit green light, the selenium precursor, the tellurium precursor and the first zinc precursor react almost completely, and no purification and extraction steps are required, thereby greatly simplifying the synthesis steps.
[0060] In some embodiments, in step S2, the selenium precursor is added prior to the tellurium precursor, and the first zinc precursor can be added in any order.
[0061] It is necessary to add the selenium precursor before adding the tellurium precursor, because the applicant has found that if the tellurium precursor is added first and then the selenium precursor, the performance of the synthesized core / quantum dot is poor; the first zinc precursor can be added first, in the middle or last among the three, with no obvious difference.
[0062] In some embodiments, the first temperature is 220-260° C., and the reaction time of the first mixed system is 15-40 min.
[0063] In some embodiments, in step S2, fatty acid, oily ligand and organic solvent are first added, vacuum is applied, the temperature is raised to 100-140° C. and maintained for 1-3 hours, and then an inert gas is introduced and the temperature is raised to the first temperature.
[0064] The fatty acid comprises at least one of palmitic acid, oleic acid, stearic acid, lauric acid and undecylenic acid.
[0065] The oily ligand comprises at least one of oleylamine, n-octylamine, tetradecylamine and hexadecylamine.
[0066] The organic solvent comprises at least one of trioctylamine, hexadecylamine, dioctylamine, hexadecane, octadecane, squalane, phenyldodecane, phenyltetradecane and phenylhexadecane.
[0067] In some embodiments, the first mixed system further includes an activator, and the activator is used to improve the reactivity of the selenium precursor and the tellurium precursor.
[0068] Further, in step S2, the activator is added first, and then the selenium precursor, the tellurium precursor and the first zinc precursor are added. The applicant has found that when the activator is added first, and then the three precursors required for synthesizing the green light ZnSeTe core are added, the reactivity of the selenium precursor and the tellurium precursor can be better improved.
[0069] The active agent includes at least one of diphenylphosphine, triphenylphosphine, tributylphosphine and tripentylphosphine.
[0070] Furthermore, the molar ratio of the active agent added to the tellurium precursor is (2-4): 1. Preferably, the molar ratio of the active agent added to the tellurium precursor is (2.5-3.5):1.
[0071] The first mixed system of the present application also contains an activator, which can increase the reactivity of the selenium precursor and the tellurium precursor, making the distribution of Se and Te in the core more uniform, further reducing the half-peak width of the quantum dots, improving the crystallinity, and improving the photoluminescence performance and electroluminescent device performance.
[0072] In some embodiments, at the first temperature, an etchant is added to the reaction system, and the etchant is used to etch the green light ZnSeTe core.
[0073] The etchant includes fluoride, and the fluoride includes at least one of hydrofluoric acid, phenylcarbonyl fluoride, sodium fluoride, lead tetrafluoride, aluminum fluoride, tetrabutylammonium fluoride, and cesium fluoride.
[0074] By using an etchant to etch the green light ZnSeTe core, the surface oxidation state of the green light ZnSeTe core is greatly reduced, thereby improving the performance of the final quantum dot product; at the same time, the additional fluoride ions can also serve as surface ligands to reduce the amount of carboxylic acid ligands on the surface of the quantum dots, which is beneficial to hole transport in QLEDs.
[0075] In some embodiments, the method for preparing green light ZnSeTe quantum dots further comprises the steps of:
[0076] S3, preparing a transition layer: at a second temperature, adding a second zinc precursor and a selenium precursor to S2, wherein the selenium precursor is added dropwise at a rate of 4-6 mL / h to form a ZnSe transition layer covering the green light ZnSeTe core body;
[0077] S4, preparing an outer shell layer: at a third temperature, adding a third zinc precursor and a sulfur precursor to S3, wherein the third zinc precursor is an amine-containing zinc precursor, to form a ZnS outer shell layer covering the transition layer.
[0078] In some embodiments, the second zinc precursor includes at least one of zinc oleate, zinc carbonate, zinc oxide, zinc palmitate, zinc laurate, and zinc n-hexanoate.
[0079] In some embodiments, in step S3, the second temperature is 300-330°C, and the molar ratio of the added selenium precursor to the second zinc precursor is 1:(1.2-4). Preferably, the molar ratio of the added selenium precursor to the second zinc precursor is 1:(1.5-2.5).
[0080] Further, at the second temperature, 2 / 5-4 / 5 of the second zinc precursor is added, and then the selenium precursor is added dropwise at a rate of 4-6 mL / h. When the selenium precursor is added to half, the remaining second zinc precursor is added.
[0081] When preparing the ZnSe transition layer, the present application drips the selenium precursor at a rate of 4-6mL / h, and the transition layer grows little by little, and the transition of the gradient alloy layer is very slow. The band gap energy value of the transition layer is between the core body and the shell layer, thereby increasing the lattice adaptability. However, the present application makes the transition layer grow slowly, and the band gap energy grows in a curve (such as the LM curve), so that the increase of the band gap energy is slower, that is, the lattice adaptability is better and more stable, and at the same time, the stress is smaller, the transition layer has fewer defects, the reaction is more sufficient, and the thickness of the transition layer is increased.
[0082] In some embodiments, in step S3, after forming the ZnSe transition layer, the temperature is raised to 320-340°C, and a second zinc precursor and a sulfur precursor are added to form a ZnSe transition layer-coated ZnSe 1-x S xTransition layer, 0<X<1; wherein the molar ratio of the added sulfur precursor to the second zinc precursor is 1:(1.5-4), and the sulfur precursor is added dropwise at a rate of 5-7 mL / h. Preferably, the molar ratio of the added sulfur precursor to the zinc precursor is 1:(1.5-2.5).
[0083] Further, when the temperature reaches 320-340° C., 2 / 5-4 / 5 of the second zinc precursor is added, and then the sulfur precursor is added dropwise at a rate of 5-7 mL / h. When the sulfur precursor is added halfway, the remaining second zinc precursor is added.
[0084] The sulfur precursor includes at least one of dodecanethiol, hexadecanethiol, sulfur-trioctylphosphine (S-TOP), sulfur-tributylphosphine (S-TBP), sulfur-triphenylphosphine (S-TPP), and sulfur-trioctylamine (S-TOA).
[0085] On the one hand, since the amount of selenium precursor added in the synthesis of the ZnSe transition layer is excessive, the remaining selenium precursor participates in the ZnSe 1-x S x Synthesis of transition layer to form ZnSe 1-x S x On the other hand, high temperature causes Se in the ZnSe transition layer to migrate outward, participating in the ZnSe 1-x S x Synthesis of transition layer. And, with the ZnSe 1-x S x As the thickness of the transition layer increases, its X value increases (i.e., the proportion of S gradually increases). 1-x S x The transition layer makes the band gap energy increase more smoothly, that is, the lattice adaptability is better and more stable, the lattice defects are fewer, and the optical properties are better. At the same time, the sulfur precursor is added at a rate of 6-10mL / h, and ZnSe 1-x S x The bandgap energy of the transition layer slowly increases, further improving the optical performance.
[0086] In some embodiments, in step S4, the third temperature is 240-290°C, the amine-containing zinc precursor is added dropwise at a rate of 28-32 mL / h, and the sulfur precursor is added dropwise at a rate of 6-10 mL / h to form a ZnS outer shell layer.
[0087] Further, the molar ratio of the sulfur precursor to the amine-containing zinc precursor is 1:(0.5-1.5). Preferably, the molar ratio of the sulfur precursor to the amine-containing zinc precursor is 1:(0.6-0.8).
[0088] Furthermore, the amine-containing zinc precursor includes at least one of zinc oleylamine (Zn / OlAm), zinc n-octylamine, zinc tetradecylamine, and zinc hexadecylamine.
[0089] When preparing the ZnS outer shell, the reaction activity of synthesizing the ZnS shell will be greatly reduced, and it is not easy to grow the outer shell. When preparing the ZnS outer shell in the present application, the zinc precursor is an amine-containing zinc precursor, and the amine-containing zinc precursor does not solidify in the dripping pipe (the temperature in the pipe is 25°C room temperature), so the amine-containing zinc precursor can be added in a dripping manner to increase the reaction activity and make the outer shell easy to grow. In addition, after the synthesis is completed and the temperature drops to room temperature, the oleic acid ligand will replace the amine substance of the amine-containing zinc precursor, and the oleic acid ligand will bind more strongly to the quantum dots at room temperature.
[0090] In some embodiments, the preparation method further comprises step: S5, adding the amine-containing zinc precursor and the thiol ligand to step S4 to increase the thickness of the ZnS outer shell layer.
[0091] Furthermore, in step S5, the amine-containing zinc precursor is added dropwise at a rate of 22-26 mL / h, and the thiol ligand is added dropwise at a rate of 2-5 mL / h.
[0092] Further, the molar ratio of the thiol ligand added to the amine-containing zinc precursor is 1:(0.8-3). Preferably, the molar ratio of the thiol ligand added to the amine-containing zinc precursor is 1:(0.8-1.5).
[0093] The thiol ligand comprises at least one of methyl mercaptan, ethyl mercaptan, propyl mercaptan, butyl mercaptan, pentyl mercaptan, hexyl mercaptan, octyl mercaptan, dodecanethiol, hexadecanethiol, octadecanethiol and benzyl mercaptan.
[0094] After preparing the ZnS outer shell layer, the present application further adds step S5. On the one hand, the thiol ligand can be decomposed and used as a sulfur source to continue to generate ZnS, thereby increasing the thickness of the ZnS outer shell layer; on the other hand, the thiol ligand, as a ligand, has a stronger binding force than the oleic acid ligand, thereby increasing the coverage and binding firmness of the ligand.
[0095] In some embodiments, the maximum emission peak wavelength of the green light ZnSeTe quantum dots is 500-540 nm. Preferably, the maximum emission peak wavelength of the green light ZnSeTe quantum dots is 515-535 nm. More preferably, the maximum emission peak wavelength of the green light ZnSeTe quantum dots is 520-530 nm.
[0096] In a second aspect of the present application, a green light ZnSeTe quantum dot is provided, wherein the green light ZnSeTe quantum dot is prepared by the above method.
[0097] In some embodiments, the maximum emission peak wavelength of the green light ZnSeTe quantum dots is 500-540 nm. Preferably, the maximum emission peak wavelength of the green light ZnSeTe quantum dots is 515-535 nm. More preferably, the maximum emission peak wavelength of the green light ZnSeTe quantum dots is 520-530 nm.
[0098] According to a third aspect of the present application, a display device is provided, comprising the above-mentioned green light ZnSeTe quantum dots.
[0099] Display devices include: display devices, light emitting diodes (LEDs), organic light emitting diodes (OLEDs), quantum dot LEDs, quantum dot films, sensors, solar cells, image sensors, or liquid crystal displays (LCDs). Display devices include: electronic paper, mobile phones, tablet computers, televisions, monitors, laptop computers, digital photo frames, navigation systems, car displays, AR displays, and VR displays.
[0100] In addition to the core-shell quantum dot film, the display device may also include structures known to those skilled in the art in the technical field of the present invention. That is, the present invention includes a display device to which the core-shell quantum dot film of the present invention can be applied.
[0101] The present invention will be further described in detail below in conjunction with specific embodiments and comparative examples, but the present invention is not limited to the following embodiments. The implementation conditions used in the embodiments can be further adjusted according to different requirements of specific use, and the unspecified conditions are conventional conditions in the industry.
[0102] Embodiment 1:
[0103] Preparation of nuclear bodies:
[0104] In a 250mL three-necked flask, quickly add 1.02g palmitic acid (PA, 4mMol / L), 5mL oleylamine (OlAm), 20mL trioctylamine (TOA), evacuate, heat to 120℃, and maintain vacuum for 2h; introduce Ar, set the reaction temperature to 240℃, and start heating. When the temperature reaches 240℃, quickly inject 1mL diphenylphosphine (DPP), 0.5mL selenium-trioctylphosphine (Se-TOP, 2Mol / L), 3.5mL tellurium-trioctylphosphine (Te-TOP, 0.1Mol / L), and 2.5mL dimethylzinc (1.5Mol / L) in sequence, react for 25min, and form green light ZnSeTe core.
[0105] Preparation of ZnSe transition layer and ZnSe 1-x S x Transition layer:
[0106] Quickly add 0.1 mL of hydrofluoric acid-acetone solution (HF-acetone, 10% HF, 90% acetone) to the reaction system (i.e., a 250 mL three-necked flask, the same below) and react for 1 min. Heat to 310°C and quickly add 20 mL of zinc oleate (Zn(OA) 2 , 0.71Mol / L); when the temperature reached 310°C again, 5mL of selenium-trioctylphosphine (Se-TOP, 2Mol / L) was added dropwise at a rate of 6mL / h using a syringe pump; when half of the selenium-trioctylphosphine was added, 10mL of zinc oleate (Zn(OA) 2 , 0.71Mol / L), forming a ZnSe transition layer and obtaining a ZnSeTe / ZnSe structure.
[0107] After the addition of selenium-trioctylphosphine was completed, 10 mL of zinc oleate (Zn(OA)) was quickly added to the reaction system. 2 , 0.71Mol / L); the temperature reached 320°C, and 4mL of sulfur-trioctylphosphine (S-TOP, 2Mol / L) was added dropwise at a rate of 7mL / h using a syringe pump; when half of the sulfur-trioctylphosphine was added, 10mL of zinc oleate (Zn(OA) 2 , 0.71Mol / L), forming ZnSe 1-x S x Transition layer, obtain ZnSeTe / ZnSe / ZnSe 1-x S x structure.
[0108] Preparation of ZnS outer shell:
[0109] After the above-mentioned sulfur-trioctylphosphine was added, the temperature was lowered to 250°C, and 25 mL of n-octylamine zinc (0.5 Mol / L) was added to the reaction system at a rate of 31 mL / h using a syringe pump. At the same time, 10 mL of sulfur-trioctylphosphine (S-TOP, 2 Mol / L) was added to the reaction system at a rate of 9 mL / h using a syringe pump.
[0110] Keeping at 250°C, add 10 mL of n-octylamine zinc to the reaction system at a rate of 24 mL / h using a syringe pump, and at the same time add 1 mL of n-dodecyl mercaptan (DDT) to the reaction system at a rate of 3 mL / h using a syringe pump. After the reaction is completed, stop heating and allow the reaction solution to cool to room temperature. A ZnS shell layer is formed to obtain ZnSeTe / ZnSe / ZnSe 1-x S x / ZnS structure, that is, green light ZnSeTe quantum dots.
[0111] Embodiment 2:
[0112] Preparation of nuclear bodies:
[0113] In a 250mL three-necked flask, quickly add 1.02g palmitic acid (PA, 4mMol / L), 5mL oleylamine (OlAm), 20mL trioctylamine (TOA), evacuate, heat to 120℃, and maintain vacuum for 2h; introduce Ar, set the reaction temperature to 240℃, and start heating. When the temperature reaches 240℃, quickly inject 1mL diphenylphosphine (DPP), 0.5mL selenium-trioctylphosphine (Se-TOP, 2Mol / L), 3.5mL tellurium-trioctylphosphine (Te-TOP, 0.1Mol / L), 2.5mL diethylzinc (DEZ, 1Mol / L) in sequence, react for 25min, and form green light ZnSeTe core.
[0114] Preparation of ZnSe transition layer and ZnSe 1-x S x Transition layer:
[0115] Quickly add 0.1 mL of hydrofluoric acid-acetone solution (HF-acetone, 10% HF, 90% acetone) to the reaction system (i.e., a 250 mL three-necked flask, the same below) and react for 1 min. Heat to 310°C and quickly add 20 mL of zinc oleate (Zn(OA) 2 , 0.71Mol / L); when the temperature reached 310°C again, 5mL of selenium-trioctylphosphine (Se-TOP, 2Mol / L) was added dropwise at a rate of 5mL / h using a syringe pump; when half of the selenium-trioctylphosphine was added, 10mL of zinc oleate (Zn(OA) 2 , 0.71Mol / L), forming a ZnSe transition layer and obtaining a ZnSeTe / ZnSe structure.
[0116] After the addition of selenium-trioctylphosphine was completed, 10 mL of zinc oleate (Zn(OA)) was quickly added to the reaction system. 2 , 0.71Mol / L); the temperature reached 330°C, and 4mL of sulfur-trioctylphosphine (S-TOP, 2Mol / L) was added dropwise at a rate of 6mL / h using a syringe pump; when half of the sulfur-trioctylphosphine was added, 10mL of zinc oleate (Zn(OA) 2 , 0.71Mol / L), forming ZnSe 1-x S x Transition layer, obtain ZnSeTe / ZnSe / ZnSe 1-x S x structure.
[0117] Preparation of ZnS outer shell:
[0118] After the above-mentioned sulfur-trioctylphosphine was added, the temperature was lowered to 250°C, and 28 mL of zinc oleylamine (Zn / OlAm, 0.4 Mol / L) was added to the reaction system at a rate of 28 mL / h using a syringe pump, and at the same time, 7 mL of sulfur-trioctylphosphine (S-TOP, 2 Mol / L) was added to the reaction system at a rate of 7 mL / h using a syringe pump.
[0119] Keeping at 250°C, add 8 mL of zinc oleylamine (Zn / OlAm, 0.4 Mol / L) to the reaction system at a rate of 24 mL / h using a syringe pump, and at the same time add 1 mL of n-dodecyl mercaptan (DDT) to the reaction system at a rate of 3 mL / h using a syringe pump. After the reaction is completed, stop heating and allow the reaction solution to cool to room temperature. A ZnS shell layer is formed to obtain ZnSeTe / ZnSe / ZnSe 1-x S x / ZnS structure, that is, green light ZnSeTe quantum dots.
[0120] Comparative Example 1:
[0121] Preparation of nuclear bodies:
[0122] In a 300 milliliter (mL) reaction flask, palmitic acid was dissolved in trioctylamine and heated at 120°C under vacuum. After one hour, the atmosphere in the flask was replaced with an inert gas (nitrogen), and the reaction flask was heated to 300°C. Selenium-trioctylphosphine (Se-TOP, 2Mol / L), tellurium-trioctylphosphine (Te-TOP, 0.5Mol / L) and zinc oleate (0.71Mol / L) were quickly injected into the flask, and the reaction was carried out for 60 minutes. Wherein, the molar ratio between the zinc precursor and the selenium precursor was 2: 1 (Zn: Se), and the molar ratio between the selenium precursor and the tellurium precursor was 4.5: 1 (Se: Te). The reactor was cooled to room temperature and acetone was added to promote the formation of a precipitate, which was centrifuged to obtain a green light ZnSeTe nucleus, which was then dispersed in toluene.
[0123] Preparation of ZnSe transition layer:
[0124] To a 300mL reaction flask, trioctylamine (TOA), zinc acetate and oleic acid were added, and the mixture was vacuum treated at 120°C for one hour, and the atmosphere in the flask was replaced with an inert atmosphere (nitrogen). When the flask was heated to a temperature of 300°C, the green light ZnSeTe nucleus was quickly added, followed by selenium-trioctylphosphine (Se-TOP, 2Mol / L), and the reaction was carried out for 120 minutes. Wherein, the molar ratio between the zinc precursor and the selenium precursor was about 2.85:1.5. The flask was cooled to room temperature, and acetone was added to promote the formation of a precipitate, and separated via centrifugation to obtain a ZnTeSe / ZnSe core-shell structure, which was then dispersed in toluene.
[0125] Preparation of ZnS outer shell:
[0126] To a 300 mL reaction flask, trioctylamine (TOA), zinc acetate and oleic acid were added, and the mixture was vacuum treated at 120 ° C for one hour, and the atmosphere in the flask was replaced with nitrogen. The flask was cooled to 250 ° C, and the ZnTeSe / ZnSe core-shell structure was quickly added, and then sulfur-trioctylphosphine (S-TOP, 2Mol / L) was added and reacted for 60 minutes. Among them, the molar ratio between the zinc precursor and the sulfur precursor was 2: 1. The flask was cooled to room temperature, and acetone was added to promote the formation of a precipitate, and separated by centrifugation to obtain a ZnTeSe / ZnSe / ZnS core-shell structure, i.e., green light ZnSeTe quantum dots.
[0127] Photoluminescence (PL) performance:
[0128] The green light ZnSeTe quantum dots of Examples 1-2 and Comparative Example 1 were respectively tested for their photoinduced maximum emission peak wavelength and half-maximum width (FWHM) using a hatichi F4500 fluorescence spectrophotometer, and their quantum efficiency (QY) was respectively tested using a fluorescence quantum efficiency meter. The test results are shown in Table 1.
[0129] Table 1: Photoluminescence performance test results of embodiments and comparative examples.
[0130]
[0131] It can be seen from Table 1 that the green light ZnSeTe quantum dots of Example 1-2 have a narrow emission linewidth (the photoinduced maximum emission peak wavelength is 525±5nm); the particle size of the green light ZnSeTe quantum dots is uniform, and the FWHM value is significantly lower than that of Comparative Example 1; and the quantum efficiency QY is significantly better than that of Comparative Example 1.
[0132] Electroluminescence (EL) performance:
[0133] The green ZnSeTe quantum dots of Examples 1-2 and Comparative Example 1 are used to prepare electroluminescent devices respectively, and the steps are as follows:
[0134] The green light ZnSeTe quantum dots are mixed with a photoresist and spin-coated to form a green light ZnSeTe light-emitting layer;
[0135] Providing a flexible substrate on which an ITO conductive layer is formed;
[0136] Spin-coat a PEDOT:PSS layer, a PF8 layer, and a green light ZnSeTe luminescent layer on the ITO conductive layer in sequence;
[0137] A ZnO electron transport layer is spin-coated on the green ZnSeTe light-emitting layer;
[0138] An Al layer is evaporated on the ZnO electron transport layer;
[0139] The electroluminescent device is encapsulated by using encapsulation glue.
[0140] The electroluminescent devices prepared in Examples 1-2 and Comparative Example 1 were tested for the maximum emission peak wavelength, half-maximum width (FWHM), maximum external quantum efficiency at 2000 nits (EQE@2000nits), current efficiency at 2000 nits (CE@2000nits), brightness at 4 V (L@4V) and current density at 4 V (J@4V) using a Spectra Scan PR-655 instrument. The test results are shown in Table 2.
[0141] Table 2: Electroluminescent performance test results of embodiments and comparative examples.
[0142]
[0143] It can be seen from Table 2 that the green light ZnSeTe quantum dots of Example 1-2 have a narrow emission linewidth (the photoinduced maximum emission peak wavelength is 525±5nm); the particle size of the green light ZnSeTe quantum dots is uniform, and the FWHM value is significantly lower than that of Comparative Example 1; and the electroluminescent properties such as maximum external quantum efficiency EQE and brightness are significantly better than those of Comparative Example 1.
[0144] Although the present application has disclosed multiple aspects and embodiments, other aspects and embodiments will be obvious to those skilled in the art, and several modifications and improvements may be made without departing from the concept of the present application, all of which belong to the protection scope of the present application. The multiple aspects and embodiments disclosed in the present application are only for illustration and are not intended to limit the present application. The actual protection scope of the present application shall be subject to the claims.
Claims
1. A method for preparing green light ZnSeTe quantum dots, characterized in that: The preparation method comprises the steps of: S1, obtaining a selenium precursor, a tellurium precursor and a first zinc precursor, wherein the reaction activity of the first zinc precursor is higher than that of the selenium precursor and the tellurium precursor; S2, at a first temperature, mixing a selenium precursor, a tellurium precursor and a first zinc precursor to form a first mixed system, wherein the molar ratio of the selenium precursor, the tellurium precursor and the first zinc precursor is (1-4):1:(7-10), and reacting to generate a green light ZnSeTe nucleus.
2. The method for preparing green light ZnSeTe quantum dots according to claim 1, characterized in that: Includes one or more features selected from the following group: (1) The first zinc precursor includes at least one of dimethyl zinc, diethyl zinc, zinc acetate, zinc acetylacetonate, and zinc fluoride; (2) In step S2, the molar ratio of the selenium precursor, the tellurium precursor and the first zinc precursor added is (2.5-3.5):1:(8-9); (3) In step S2, the selenium precursor is added before the tellurium precursor, and the first zinc precursor can be added in any order; (4) The first temperature is 220-260° C., and the reaction time of the first mixed system is 15-40 min.
3. The method for preparing green light ZnSeTe quantum dots according to claim 1, characterized in that: The first mixed system further includes an activator, and the activator is used to improve the reactivity of the selenium precursor and the tellurium precursor; Preferably, in step S2, the activator is added first, and then the selenium precursor, the tellurium precursor and the first zinc precursor are added; Preferably, the active agent includes: at least one of diphenylphosphine, triphenylphosphine, tributylphosphine, and tripentylphosphine; Preferably, the molar ratio of the added activator to the tellurium precursor is (2-4):
1.
4. The method for preparing green light ZnSeTe quantum dots according to claim 1, characterized in that: The method for preparing green light ZnSeTe quantum dots also includes the steps of: S3, preparing a transition layer: at a second temperature, adding a second zinc precursor and a selenium precursor to S2, wherein the selenium precursor is added dropwise at a rate of 4-6 mL / h to form a ZnSe transition layer covering the green light ZnSeTe core body; S4, preparing an outer shell layer: at a third temperature, adding a third zinc precursor and a sulfur precursor to S3, wherein the third zinc precursor is an amine-containing zinc precursor, to form a ZnS outer shell layer covering the transition layer.
5. The method for preparing green light ZnSeTe quantum dots according to claim 4, characterized in that: In step S3, the second temperature is 300-330°C, and the molar ratio of the added selenium precursor to the second zinc precursor is 1:(1.2-4); Preferably, in step S3, after forming the ZnSe transition layer, the temperature is raised to 320-340°C, and a second zinc precursor and a sulfur precursor are added to form a ZnSe coating on the ZnSe transition layer. 1-x S x Transition layer, 0<X<1; wherein the molar ratio of the added sulfur precursor to the second zinc precursor is 1:(1.5-4), and the sulfur precursor is added dropwise at a speed of 5-7 mL / h.
6. The method for preparing green light ZnSeTe quantum dots according to claim 4, characterized in that: In step S4, the third temperature is 240-290° C., the amine-containing zinc precursor is added dropwise at a rate of 28-32 mL / h, and the sulfur precursor is added dropwise at a rate of 6-10 mL / h to form a ZnS outer shell layer; the molar ratio of the sulfur precursor to the amine-containing zinc precursor is 1: (0.5-1.5)。 7. The method for preparing green light ZnSeTe quantum dots according to claim 4, characterized in that: The method for preparing green light ZnSeTe quantum dots also includes the steps of: S5, adding the amine-containing zinc precursor and the thiol ligand to step S4 to increase the thickness of the ZnS outer shell layer; Preferably, in step S5, the amine-containing zinc precursor is added dropwise at a rate of 22-26 mL / h, and the thiol ligand is added dropwise at a rate of 2-5 mL / h; the molar ratio of the thiol ligand to the amine-containing zinc precursor is 1:(0.8-3).
8. The method for preparing green light ZnSeTe quantum dots according to claim 6, characterized in that: The maximum emission peak wavelength of the green light ZnSeTe quantum dots is 500-540nm; Preferably, the maximum emission peak wavelength of the green light ZnSeTe quantum dots is 520-530 nm.
9. A green light ZnSeTe quantum dot, characterized in that: The green light ZnSeTe quantum dots are obtained by the preparation method described in any one of claims 1-8.
10. A display device, characterized in that: The display device comprises the green light ZnSeTe quantum dots as claimed in claim 9.